Production of brick type product based on carrot (Daucus Carota L.) (Research, Society and Development, 2019)
In recent years the population has generally increased the demand for foods that, besides being tasty, contain functional properties, that is to say, they have benefits to human health, which generates in the food industry the need to develop new products to meet the needs of the consumer, as for example brigadeiros from nutritious foods. In this sense, the objective of this study was to elaborate and verify the acceptance of a carrot-based brigadeiro (Daucus carota L.). This is an experimental research developed in the laboratories of Dietetic Technique and Food Sensory Analysis of the University Center of Science and Technology of Maranhão - UNIFACEMA, located in the city of Caxias - MA. The sensorial analysis of the product was performed with untrained assessors to test acceptance with a mixed hedonic scale of 9 points, by signing the TCLE. The microbiological analysis was determined according to the microbiological standards established by the current legislation. It was observed that there was no significant difference between the samples in relation to the evaluated attributes and the level of acceptance. The sensorial analysis allowed to verify that the three samples obtained a good index of acceptance by the tasters. Therefore the carrot-based brigadeiro (Daucus carota L.) is an innovative product with good acceptability, with possible nutritional and functional properties.